Complication Rates Following Septoplasty With Inferior Turbinate Reduction - Joshi, Rina R. (Ochsner J, 2019)
Background: Septoplasty with submucous resection of the inferior turbinate (SMRT) is a common correctional surgery performed in patients with deviated nasal septum resulting in nasal obstruction. Although complications are infrequent, studies examining long-term complications following septoplasty with SMRT are rare. Methods: We conducted a retrospective review of patients electing to undergo septoplasty with SMRT at a tertiary rhinology clinic from January 2007 to December 2015. Demographic data, intraoperative findings, duration of follow-up, and short-term and long-term complications were collected. Exclusion criteria included patients who underwent either septoplasty or turbinate reduction or any other nasal surgery, patients lost to follow-up within 1 year, and patients with incomplete medical records. Results: A total of 359 patients met inclusion criteria. The majority were males (66.6%), and the average age of the cohort was 36.8 ± 12.3 years. The mean follow-up time was 23.3 months. Short-term complications were postoperative infection (n=12, 3.3%) and epistaxis that required intervention (n=16, 4.5%). Long-term complications occurred in 10 patients (2.8%): revision septoplasty (n=9, 2.5%) and hyposmia (n=1, 0.3%). No instances of synechiae, septal perforation, or saddle nose deformity occurred. Conclusion: Long-term complications following septoplasty with SMRT are infrequent. The most common long-term complication in this cohort was revision septoplasty.